Childhood and adolescent risk and protective factors for violence in adulthood. (June 2016) - Dubow, Eric F.; Huesmann, L. Rowell; Boxer, Paul; Smith, Cathy
Abstract: Purpose: We use data from a community sample followed from ages 8 to 48. We focus on the main and risk-buffering effects of childhood and adolescent protective factors for predicting adulthood violence (official records and self reports). Method: Males (N = 436) from the Columbia County Longitudinal Study participated. The youth, their parents, and peers were first interviewed when the youth were age 8; the youth were later interviewed at ages 19, 30, and 48. Results: Risk factors for adulthood violence included higher aggression and lower family socioeconomic status at ages 8 and 19. Protective factors included anxiety about behaving aggressively (ages 8 and 19), popularity (ages 8 and 19), family church attendance (age 8), lower negative family interactions (age 8), and higher educational aspirations (age 19). For youth with at least one risk factor, the sum of adolescent—but not childhood–protective factors reduced the likelihood of adulthood violence. The most critical adolescent risk-buffering protective factors were anxiety about behaving aggressively and educational aspirations. Conclusions: Aggression and low family SES, even by age 8, place youth at risk for adulthood violence. Interventions to strengthen critical protective factors must continue into late adolescence to reduce the likelihood of adulthood violence among at-risk youth. Highlights: Data come from a community sample followed from ages 8 to 48. Childhood aggression and low family SES placed youth at risk for adulthood violence. Adolescent protective factors reduced the likelihood of adulthood violence.